CRISPR for accelerating genetic gains in under-utilized crops of the drylands: Progress and prospects - Sharma, Kiran K.; Palakolanu, Sudhakar Reddy; Bhattacharya, Joorie; Shankhapal, Aishwarya R.; Bhatnagar-Mathur, Pooja (Frontiers in Genetics, 2022)
Technologies and innovations are critical for addressing the future food system needs and genetic resources are essential to that change process. Integrating advanced breeding tools like “genome editing” for modernizing crop breeding are vital to provide game-changing solutions to some of the “must needed” traits in agriculture. CRISPR/Cas tool dominate site-directed nucleases (SDNs) such as ZFNs and TALENs for its accessibility and efficiency and have been rapidly repurposed for editing applications based on improved efficiency, specificity and reduced off-targets. Additionally, precise gene-editing tools such as base editing, prime editing and multiplexing provide precision for stacking of multiple traits in an elite variety, facilitating specific and targeted crop improvement, and advancing research and delivery of products in a short time span, thereby enhancing the rate of genetic gains. This review sheds light on tissue culture-free techniques for editing. A special focus has placed on food security in the drylands through crops including millets, teff, fonio, quinoa, Bambara groundnut, pigeonpea and cassava. While these crops contribute significantly to the agricultural economy and resilience of the dryland, improvement of several traits including increased stress tolerance, nutritional value and yields are urgently required. Finally, the scope of regulatory issues has been stated, implying the dire impacts of unreasonable scrutiny of genome-edited plants on the evolution and progress of the much-needed technological advances.